Il vincolo della bilancia dei pagamenti come elemento di spiegazione delle differenze internazionali dei tassi di sviluppo - A.P. THIRLWALL (Moneta e Credito, 2014)
The neo-classical approach to the question of why growth rates differ between countries concentrates on the supply side of the economy using the concept of the production function. While this approach is fruitful, it does little to explain why the growth of factor supplies and productivity differs between countries. The present paper shows how closely the growth experience of several developed countries approximates to the rate of growth exports divided by the income elasticity of demand for imports, which, on certain assumptions, can be regarded as a measure of what the author calls the balance of payments equilibrium growth rate. The hypothesis proposed is that if balance of payments equilibrium must be maintained, a country’s long run growth rate will be determined by the ratio of its rate of growth of exports to its income elasticity of demand for imports.